The challenges of novice primary school heads in Mauritius - Belle Louis Jinot; Balkooram Madhuree (Intelektual Pustaka Media Utama, 2020)
The paper aims to contribute to the limited literature on the challenges faced particularly by the primary school headmasters. It contextualizes the problem to the current educational reform in Mauritius. The mixed-methods approach was adopted to examine the daily experiences of headmasters in three selected primary schools. A semi-structured questionnaire was administered with 100 teachers to analyse the challenges experienced by their novice headmasters, and the novice school head of each of these schools was interviewed to explore the reasons behind these challenges. The novice heads suffered from professional isolation; they are overwhelmed with administrative management; their incapacity to manage learner discipline due to lack of parental support in implementing the reform; and they cannot support the implementation of digitalized education. The study was limited to the perceptions of teachers about the challenges met by their novice headmasters. An in-depth interview with these novice school heads would have provided other challenges that were more important to them in their leadership practice, or a survey with a large sample of novice headmasters would have added more input to the study. Implications are provided for the novice school heads and for the Ministry of Education to look into the possibilities for professional development opportunities in school leadership. As a unique study into the challenges of novice school heads in the primary school context, it offers insights to the educational authorities who would be able to design a framework of school leadership for this neglected category of heads.